Epigenetic regulation of oligodendrocyte differentiation: From development to demyelinating disorders. Issue 8 (10th March 2020) - Samudyata,; Castelo‐Branco, Gonçalo; Liu, Jia
Abstract: The maintenance of progenitor states or the differentiation of progenitors into specific lineages requires epigenetic remodeling of the gene expression program. In the central nervous system, oligodendrocyte progenitors (OPCs) give rise to oligodendrocytes (OLs), whose main function has been thought to be to produce myelin, a lipid‐rich structure insulating the axons. However, recent findings suggest diverse OL transcriptional states, which might imply additional functions. The differentiation of OPCs into postmitotic OLs is a highly regulated and sensitive process and requires temporal waves of gene expression through epigenetic remodeling of the genome. In this review, we will discuss recent advances in understanding the events shaping the chromatin landscape through histone modifications and long noncoding RNAs during OPC differentiation, in physiological and pathological conditions. We suggest that epigenetic regulation plays a fundamental role in governing the accessibility of transcriptional machinery to DNA sequences, which ultimately determines functional outcomes in OLs. Main points: Oligodendrocyte progenitor cell differentiation is mediated by crosstalk between transcription factors (TFs), histone modifying enzymes, chromatinremodeling complexes (CRCs), and long noncoding RNAs. Histone modifications play a fundamental role in shaping the chromatin landscape in OPC differentiation.